Comparative Candidates Survey (CCS) Wave II - Cumulative Dataset 2013 - 2018 - Binder, Tanja; Lauener, Lukas; Lindholm, Annika; Lutz, Georg; Pekari, Nicolas; Rosset, Jan; Tresch, Anke (FORS - Swiss Centre of Expertise in the Social Sciences, 2018)
The Comparative Candidate Survey (CCS) is a response to the growing number of candidate surveys in the Anglo-saxon world and beyond. More or less regular candidate surveys are conducted in Australia, Germany, the Netherlands, New Zealand, the United Kingdom, and the United States. The rational of the CCS is to harmonise these dispersed efforts and give them a cross-nationally comparable core. The CCS is an internationally coordinated effort. It combines an internationally agreed and locally adapted core questionnaire with questions that try to capture national and election specifics. The core candidate questionnaire specifically focuses on the issue of individualisation of electoral campaigns, i.e. the empirical question to which extent the candidates run their own campaigns distinct from those of their parties. CCS has been running since 2006. Using the CCS wave I questionnaire, the first wave includes candidate surveys from 32 elections across 24 countries. To date, the second wave incorporates candidate surveys from 18 parliamentary elections in 17 countries, where the CCS wave II questionnaire was used. More information on the project can be found on the CCS website (www.comparativecandidates.org). : Face-to-face interview (CAPI, CAMI, PAPI, etc.) : Entretien en face-à-face (CAPI, CAMI, PAPI, etc.) : Befragung Face-to-Face (CAPI, CAMI, PAPI etc.) : Self-administered questionnaire: Paper : Questionnaire auto-administré: papier : Selbst ausgefüllter Fragebogen: Papier : Self-administered questionnaire: Web-based : Questionnaire auto-administré: par Internet : Selbst ausgefüllter Fragebogen: internetbasiert : Candidates for parliamentary elections in Albania, Australia, Belgium, Canada, Chile, Estonia, Finland, Germany, Greece, Hungary, Iceland, Portugal, Romania, Montenegro, Norway, Sweden, and Switzerland.